Analisis Kebijakan Pada UMKM Bintan Snack Millennium Dalam Meningkatkan Efisiensi Proses Bisnis - Shinta Dewi; Jeslin Jeslin; Kristina Kristina; Sherry Sherry; Angeline Aurellia (Jurnal Cakrawala Ilmiah, 2022)
This study aims to analyze the various policies that exist in Bintan Snack Millennium MSME in a way to increase efficiency which also affects productivity and income. The primary data used is valid data taken from the results of observations and interviews with Bintan Snack Millennium MSME. The results showed that the Bintan Snack Millennium MSME still had several problems that were known to hinder the company's progress, but they could be handled well by implementing the existing policies. This has a positive effect on development and improves the efficiency of the company's business processes. It is hoped that the Bintan Snack Millennium MSME will continue to maintain the current policies and add policies such as ESG or CSR principles and contribute to the SDGs to improve MSME performance.